Longitudinal monitoring of CA125 levels provides additional information about survival in ovarian cancer - Gupta Digant; Lammersfeld Carolyn A; Vashi Pankaj G; Braun Donald P (BMC, 2010)
Abstract Background We investigated the prognostic impact of changes in serum CA125 levels during the first 3 months of therapy in ovarian cancer. Methods A case series of 170 ovarian cancer patients treated at Cancer Treatment Centers of America. Based on CA125 levels at baseline and 3 months, patients were classified into 4 groups: 1) Normal (0-35 U/ml) at baseline and three months; 2) High (>35 U/ml) at baseline, normal at three months; 3) Normal at baseline, high at 3 months; 4) High at baseline and three months. Kaplan Meier method was used to calculate survival across the 4 categories. Results Of 170 patients, 36 were newly diagnosed while 134 had received prior treatment. 25 had stage I disease at diagnosis, 15 stage II, 106 stage III and 14 stage IV. The median age at presentation was 54.2 years (range 23.1 - 82.5 years). At baseline, 31 patients had normal (0-35 U/ml) serum CA125 levels while 139 had high (>35 U/ml) levels. At 3 months, 59 had normal while 111 had high levels. Patients with a reduced CA125 at 3 months had a significantly better survival than those with increased CA125 at 3 months. Patients with normal values of CA125 at both baseline and 3 months had the best overall survival. Conclusions These data show that reduction in CA125 after 3 months of therapy is associated with better overall survival in ovarian cancer. Patients without a significant decline in CA125 after 3 months of therapy have a particularly poor prognosis.